The Training Program Effectiveness to Improve English Pronunciation for Students with Hearing Impairments in the Elementary Level - Mohammad Abedrabbu Alkhawaldeh; Mohamad Ahmad Saleem Khasawneh (Borong Newinera Publisher, 2021)
This study aimed to determine the effect of a training program to improve English pronunciation for hard-of-hearing students. To achieve the aim of the study, the researchers used the quasi-experimental approach, and the study sample consisted of (30) students with hearing impairments from primary schools in the city of Irbid. The experimental group studied based on the training program and consisted of (15) students, and (15) students of the control group studied in the traditional way. A set of instruments has been prepared, which consists of an image-naming test and preparing a training program based on the curriculum for students to see their effectiveness in raising the level of pronunciation for students with hearing impairments in the English language. The results showed that there were statistically significant differences between the control and experimental groups in favour of the experimental group. The study recommended holding training courses (sound training) targeting parents of hearing-impaired students in order to develop the receptive and expressive language of their children.